TEACHERS’ DIFFICULTIES IN TEACHING READING COMPREHENSION OF THE SEVENTH GRADE STUDENTS - Ranico, Visa; Asnita, Roma Nur; Husnaini, Husnaini (Journal of English Education and Linguistics, 2023)
This article was conducted to find out the teachers’ difficulties in teaching reading comprehension of the seventh-grade students at SMPN 22 Palembang. The research design used in this study was descriptive qualitative method. The participants in this study were two English language teachers who teach in grade seventh at SMPN 22 Palembang. The data were collected using a semi- structured interview with open-ended questions. Then, data from interviews was analyzed using thematic analysis in this study as part of the analysis. After analyzing the data, the findings showed that there are five difficulties that teachers face when teaching reading comprehension in seventh grade students at SMPN 22 Palembang, as follows: (1) students’ lack of motivation, (2) limited instructional time, (3) lack of background knowledge (4) students’ limited vocabulary, and (5) lesson plan constraints. Therefore, this research discusses the difficulties experienced by English teachers in seventh grade, thus it is hoped that readers especially English teachers who experienced similar difficulties can use this research to increase their variety of learning activities and overcome the difficulties they are faced.